MINI POWER GENERATION USING SCREW TURBINE - Prof. Metkari A. S.,; Mr. Suyog Shirishkumar Deshmukh,; Mr. Omprakash Ganpat Doiphode,; Mr. Prasad Satish Sherkhane,; Mr. Rupesh Dinkar Chavan, (International Journal of Innovations in Engineering Research and Technology, 2023)
The main limitation in hydro power generation is continues and constant flow of the Water with high pressure. to overcome this main disadvantage screw turbine is good option The screw turbine is invented before 300 BC by Archimedes that ’s why it is also called as Archimedes screw turbine.By this project we can overcome the other hydro power generation technic draw back the main advantage of the screw turbine is it can work with low pressure water or with water full of dirt the solid contents like stone, branches etc. cannot affect the operation of screw turbine.